2014
DOI: 10.1002/asia.201402241
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of the CERT Inhibitor HPA‐12 and Some Novel Derivatives

Abstract: HPA-12 is an inhibitor of CERT-mediated non-vesicular transport of ceramide from the ER membranes to the Golgi apparatus. The inhibitor effectively blocks the synthesis of the membrane lipid sphingomyelin and may represent a novel drug prototype. Previous syntheses relied on non-commercial catalysts or specialized chemistries. Here we present a straightforward and effective method to synthesize HPA-12 from commercially available protected L-serinol in four steps. Some new analogues were synthesized and evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 22 publications
3
23
0
1
Order By: Relevance
“…[21] AT R-FRET homogeneousphase assay was specifically developed, allowing complete determination of HPA-12 EC 50 . [23] These data corroborate our evaluation with the CERT START domain that showed, on the other hand, that the cyclohexyl analogue displays ap rotein binding comparable to that of HPA-12. Crystals tructures of as eries of (1R,3R)-HPAs with C13 to C16 acyl chains in complex with the CERT START domain were reported,i ndicating ar ecognition mode very similart ot hat of the naturalc argo lipid Cer.…”
Section: Syntheses Of Hpas Analogues and Structure-activity Relationssupporting
confidence: 88%
See 3 more Smart Citations
“…[21] AT R-FRET homogeneousphase assay was specifically developed, allowing complete determination of HPA-12 EC 50 . [23] These data corroborate our evaluation with the CERT START domain that showed, on the other hand, that the cyclohexyl analogue displays ap rotein binding comparable to that of HPA-12. Crystals tructures of as eries of (1R,3R)-HPAs with C13 to C16 acyl chains in complex with the CERT START domain were reported,i ndicating ar ecognition mode very similart ot hat of the naturalc argo lipid Cer.…”
Section: Syntheses Of Hpas Analogues and Structure-activity Relationssupporting
confidence: 88%
“…Arenz and coworkers [23] Chem. HPA-12 stereoisomers Aza-Michael-based crystallization-induced asymmetric transformation EC 50 determination by TR-FRET binding assay by competition versus biotinylated-ceramide bound to STARTd omain of CERT [32] BerkeŠ,Ballereau, GØnisson and coworkers [21] Meta-orpara-substituents on phenyl ring Chelation-controlled reduction of N-protected bamino ketones Not evaluated Ramapanicker and co-workers [26] Long alkyl chain in meta-o rpara-position on aromatic ring Aza-Michael-based crystallization-induced asymmetric transformation followed by Sonogashira coupling and triple bond reduction EC 50 determination by TR-FRET binding assay by competition versus biotinylated-ceramide bound to the STARTd omain of CERT [32] Daïch, GØnisson, Berkeš and coworkers [33] Replacement of the phenyl ring by long alkyl chains Aza-Michael-based crystallization-induced asymmetric transformation followed by hydrodesulfurization of thiophene ring EC 50 determination by TR-FRET binding assay by competition versus biotinylated-ceramide bound to STARTd omain of CERT [32] Daïch, GØnisson, Berkeš and coworkers [33] Not evaluated …”
Section: C16 Bound To Certmentioning
confidence: 99%
See 2 more Smart Citations
“…10 The revised structure was confirmed using X-ray crystallographic analysis by Kobayashi et al 11 Thus the revised structure of HPA-12 has a syn-orientation of the amino and hydroxyl groups and hence methodologies for its synthesis should rely on syn-stereoselective reduction of the corresponding oxo-amino compounds. Recent reports on the synthesis of the (1R,3S) derivative of HPA-12 include a tandem approach using (S)-Wynberg lactone by Snowden et al, 12 Ru-catalyzed asymmetric rearrangement of isoxazolidines reported by Kang et al, 13 and the synthesis of HPA-12 and its analogues from serinol by Arenz et al 14 …”
Section: Introductionmentioning
confidence: 98%